Improvement of Textural Properties of Baked Chips by Sodium Caseinate-Palm Oil Emulsion - SUN Yue, ZHANG Qiaozhen, GAO Mingshuang, LIU Siyuan, WANG Lijuan (Shipin Kexue)
This study investigated the effect of sodium caseinate-palm oil emulsions prepared under different conditions on the texture and rheological properties of potato dough and the quality of potato chips. The results showed that the cohesiveness and springiness of potato dough with the addition of S-100 (sodium caseinate:oil:water = 2:4.5:228, m/m) increased, and the hardness, gumminess and chewiness decreased compared with the control group. The degradation of dough quality was significantly reduced after resting for 60 min. Moreover, the hardness of the potato chips prepared with S-100 was the smallest. This was mainly due to the fact that the emulsified palm oil was encapsulated into small droplets with an average particle size of 12.13 μm and dispersed more uniformly in the dough; moreover, sodium caseinate as a water-retaining agent retarded the loss of water in the dough while facilitating the interaction between protein and starch. The results of correlation analysis showed that increasing springiness and decreasing hardness of potato dough resulted in lower hardness of potato chips. As a result, addition of S-100 provided the most significant quality improvement of potato dough and chips.